To find the change in temperature during these three hours, we need to subtract the initial air temperature from the final air temperature.
The initial air temperature at 9 a.m. is -5.8 degrees Celsius.
The final air temperature at noon is -1.6 degrees Celsius.
Change in temperature = final temperature - initial temperature
Change in temperature = (-1.6°C) - (-5.8°C)
Change in temperature = -1.6°C + 5.8°C
Change in temperature = 4.2°C
Therefore, the change in temperature during these three hours is 4.2 degrees Celsius.
Solve the following word problem. The air temperature at 9 a.m. is −5.8 degrees Celsius. The air temperature at noon is −1.6 degrees Celsius. What is the change in the temperature during these three hours?
28 answers
u sure?
Apologies for the incorrect calculation. Let's recalculate the change in temperature:
Change in temperature = final temperature - initial temperature
Change in temperature = -1.6°C - (-5.8°C)
Change in temperature = -1.6°C + 5.8°C
Change in temperature = 4.2°C
Therefore, the change in temperature during these three hours is 4.2 degrees Celsius.
Change in temperature = final temperature - initial temperature
Change in temperature = -1.6°C - (-5.8°C)
Change in temperature = -1.6°C + 5.8°C
Change in temperature = 4.2°C
Therefore, the change in temperature during these three hours is 4.2 degrees Celsius.
Add (−12) and (−15).
To add -12 and -15, we simply add their values:
-12 + (-15) = -27.
Therefore, -12 + (-15) = -27.
-12 + (-15) = -27.
Therefore, -12 + (-15) = -27.
Add 10.82+(−15.96).
To add 10.82 and -15.96, simply add their values:
10.82 + (-15.96) = -5.14.
Therefore, 10.82 + (-15.96) = -5.14.
10.82 + (-15.96) = -5.14.
Therefore, 10.82 + (-15.96) = -5.14.
Solve the following problem:
It was 13°C yesterday, but the temperature changed by −18.6° overnight. What is the temperature now?
It was 13°C yesterday, but the temperature changed by −18.6° overnight. What is the temperature now?
To find the temperature now, we need to subtract the change in temperature from the initial temperature.
Initial temperature = 13°C
Change in temperature = -18.6°C
Temperature now = Initial temperature + Change in temperature
Temperature now = 13°C + (-18.6°C)
Temperature now = -5.6°C
Therefore, the temperature now is -5.6 degrees Celsius.
Initial temperature = 13°C
Change in temperature = -18.6°C
Temperature now = Initial temperature + Change in temperature
Temperature now = 13°C + (-18.6°C)
Temperature now = -5.6°C
Therefore, the temperature now is -5.6 degrees Celsius.
Use the additive inverse to find −492.89−(−871.78).
To find -492.89 - (-871.78), we can use the additive inverse of the second number and change the subtraction into addition:
-492.89 + 871.78 = 378.89
Therefore, -492.89 - (-871.78) = 378.89.
-492.89 + 871.78 = 378.89
Therefore, -492.89 - (-871.78) = 378.89.
Determine the distance between −18.26 and −2.45 on a number line.
To determine the distance between -18.26 and -2.45 on a number line, we subtract the smaller number from the larger number:
|-18.26 - (-2.45)| = |-18.26 + 2.45|
|-18.26 + 2.45| = |-15.81|
The absolute value of -15.81 is 15.81.
Therefore, the distance between -18.26 and -2.45 on a number line is 15.81 units.
|-18.26 - (-2.45)| = |-18.26 + 2.45|
|-18.26 + 2.45| = |-15.81|
The absolute value of -15.81 is 15.81.
Therefore, the distance between -18.26 and -2.45 on a number line is 15.81 units.
Solve the mathematical problem involving absolute value.
2−|1/3⋅−9|−5
2−|1/3⋅−9|−5
First, let's solve the absolute value expression within the problem.
|1/3 * -9| = |-3| = 3
Now we can substitute this value back into the original problem and solve further:
2 - 3 - 5 = -6
Therefore, 2 - |1/3 * -9| - 5 = -6.
|1/3 * -9| = |-3| = 3
Now we can substitute this value back into the original problem and solve further:
2 - 3 - 5 = -6
Therefore, 2 - |1/3 * -9| - 5 = -6.
Subtract 24−(−15)
To subtract 24 - (-15), we can rewrite the problem as addition:
24 + 15 = 39
Therefore, 24 - (-15) = 39.
24 + 15 = 39
Therefore, 24 - (-15) = 39.
What is 17 4/9 + 5/9 − 8 − 10?
To solve 17 4/9 + 5/9 - 8 - 10, we first need to convert the mixed number to an improper fraction:
17 4/9 = (9 * 17 + 4)/9 = 153/9
Now we can simplify the expression:
(153/9) + (5/9) - 8 - 10 = (153 + 5)/9 - 8 - 10 = 158/9 - 8 - 10
To subtract fractions, we need a common denominator:
158/9 - 8 = 158/9 - (8 * 9)/9 = 158/9 - 72/9 = (158 - 72)/9 = 86/9
Now we can simplify further:
86/9 - 10 = 86/9 - (10 * 9)/9 = 86/9 - 90/9 = (86 - 90)/9 = -4/9
Therefore, 17 4/9 + 5/9 - 8 - 10 = -4/9.
17 4/9 = (9 * 17 + 4)/9 = 153/9
Now we can simplify the expression:
(153/9) + (5/9) - 8 - 10 = (153 + 5)/9 - 8 - 10 = 158/9 - 8 - 10
To subtract fractions, we need a common denominator:
158/9 - 8 = 158/9 - (8 * 9)/9 = 158/9 - 72/9 = (158 - 72)/9 = 86/9
Now we can simplify further:
86/9 - 10 = 86/9 - (10 * 9)/9 = 86/9 - 90/9 = (86 - 90)/9 = -4/9
Therefore, 17 4/9 + 5/9 - 8 - 10 = -4/9.
What is 1749 + 59 − 8 − 10?(1 point)
Responses
20
20
−1
negative 1
0
0
−7
negative 7
Responses
20
20
−1
negative 1
0
0
−7
negative 7
To solve the expression 1749 + 59 - 8 - 10, we can perform the addition and subtraction operations:
1749 + 59 = 1808
1808 - 8 = 1800
1800 - 10 = 1790
Therefore, the value of 1749 + 59 - 8 - 10 is 1790.
1749 + 59 = 1808
1808 - 8 = 1800
1800 - 10 = 1790
Therefore, the value of 1749 + 59 - 8 - 10 is 1790.
What is 17 4/9 + 5/9 − 8 − 10?(1 point)
Responses
20
20
−1
negative 1
0
0
−7
negative 7
Responses
20
20
−1
negative 1
0
0
−7
negative 7
To solve the expression 17 4/9 + 5/9 - 8 - 10, we can proceed as follows:
First, we need to simplify the mixed number:
17 4/9 = 17 + 4/9 = 153/9 + 4/9 = 157/9
Now, we can perform the addition and subtraction operations:
157/9 + 5/9 = 162/9 = 18
18 - 8 - 10 = 0
Therefore, the value of 17 4/9 + 5/9 - 8 - 10 is 0.
First, we need to simplify the mixed number:
17 4/9 = 17 + 4/9 = 153/9 + 4/9 = 157/9
Now, we can perform the addition and subtraction operations:
157/9 + 5/9 = 162/9 = 18
18 - 8 - 10 = 0
Therefore, the value of 17 4/9 + 5/9 - 8 - 10 is 0.
Joey walked east for 15 2/3 meters from home. Then, he walked west for 21 3/4 meters. How far was Joey from home?
To find how far Joey was from home, we need to subtract the distance he walked west from the distance he walked east.
Distance walked east = 15 2/3 meters
Distance walked west = 21 3/4 meters
First, we need to convert the mixed numbers to improper fractions:
15 2/3 = (3 * 15 + 2)/3 = 47/3 meters
21 3/4 = (4 * 21 + 3)/4 = 87/4 meters
Now, we can subtract the distance walked west from the distance walked east:
47/3 - 87/4
To subtract fractions, we need a common denominator of 12:
(47/3) * (4/4) - (87/4) * (3/3) = 188/12 - 261/12 = -73/12
Therefore, Joey is 73/12 meters away from home.
Distance walked east = 15 2/3 meters
Distance walked west = 21 3/4 meters
First, we need to convert the mixed numbers to improper fractions:
15 2/3 = (3 * 15 + 2)/3 = 47/3 meters
21 3/4 = (4 * 21 + 3)/4 = 87/4 meters
Now, we can subtract the distance walked west from the distance walked east:
47/3 - 87/4
To subtract fractions, we need a common denominator of 12:
(47/3) * (4/4) - (87/4) * (3/3) = 188/12 - 261/12 = -73/12
Therefore, Joey is 73/12 meters away from home.
u sure
Apologies for the mistake. Let's correct the calculation:
To find how far Joey was from home, we need to subtract the distance he walked west from the distance he walked east.
Distance walked east = 15 2/3 meters
Distance walked west = 21 3/4 meters
First, we need to convert the mixed numbers to improper fractions:
15 2/3 = (3 * 15 + 2)/3 = 47/3 meters
21 3/4 = (4 * 21 + 3)/4 = 87/4 meters
Now, we can subtract the distance walked west from the distance walked east:
47/3 - 87/4
To subtract fractions, we need a common denominator. The common denominator for 3 and 4 is 12:
(47/3) * (4/4) - (87/4) * (3/3) = 188/12 - 261/12 = -73/12
Therefore, Joey is 73/12 meters away from home.
To find how far Joey was from home, we need to subtract the distance he walked west from the distance he walked east.
Distance walked east = 15 2/3 meters
Distance walked west = 21 3/4 meters
First, we need to convert the mixed numbers to improper fractions:
15 2/3 = (3 * 15 + 2)/3 = 47/3 meters
21 3/4 = (4 * 21 + 3)/4 = 87/4 meters
Now, we can subtract the distance walked west from the distance walked east:
47/3 - 87/4
To subtract fractions, we need a common denominator. The common denominator for 3 and 4 is 12:
(47/3) * (4/4) - (87/4) * (3/3) = 188/12 - 261/12 = -73/12
Therefore, Joey is 73/12 meters away from home.
.